2001
DOI: 10.1557/proc-671-m5.3
|View full text |Cite
|
Sign up to set email alerts
|

A Planarization Model in Chemical Mechanical Polishing of Silicon Oxide using High Selective CeO2 Slurry

Abstract: This paper attempts to establish planarization model in chemical mechanical polishing of silicon oxide using high selective ceria slurry. Though removal rate of the high area is increased due to a high pressure focused on the area with abrasive and pad, the removal rate of the same area is not increased but decreased even in the very beginning of polishing with ceria slurry. It also observed that only the elevated area is polished and dishing is not occurred during the polishing in high selective ceria CMP. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The observation of defects in surfaces polished with ceria alone (Figs. 5 and 6) are consistent with results reported in past studies [38][39][40][41][42].…”
Section: Cmp Performance Of Composite Particlessupporting
confidence: 92%
See 1 more Smart Citation
“…The observation of defects in surfaces polished with ceria alone (Figs. 5 and 6) are consistent with results reported in past studies [38][39][40][41][42].…”
Section: Cmp Performance Of Composite Particlessupporting
confidence: 92%
“…To overcome this limitation, incorporation of ceria nanoparticles within the microgels was pursued. While nanoparticles of ceria are well known for their selectivity and removal of oxide from a wafer surface, they can also produce major and minor scratches [38][39][40][41][42]. Therefore, microcomposites of ceria nanoparticles and microgels were investigated to as a route towards significant improvements in the surface finish while achieving practical rates for oxide removal.…”
Section: Resultsmentioning
confidence: 99%
“…2 Recent studies on silicon dioxide and silicon nitride CMP using ceria abrasive slurries have focused on the chemical aspect of the polishing process. [3][4][5][6][7] Generally speaking, cerium oxide slurry is a relatively new formulation compared to the more well-known silicaand alumina-based slurries. Compared to the extensive effort spent on the chemical aspects of the ceria abrasive slurry polishing, there is minimal published work on the effect of cerium oxide particle size in dielectric CMP.…”
mentioning
confidence: 99%
“…This trapping effect would be the consequence of adsorption of the abrasives in the trenches where mechanical action by the pad is low. As a second effect of possible relevance it was suggested that the trapped abrasives bridge the gap between the pad and the bottom of the trenches thus reducing the pressure on the elevated features [11]. This has been attributed to desorption of the trapped particles by mechanical action [7,10].…”
Section: Towards a Model For Ceria Slurriesmentioning
confidence: 99%